Revealing buried interfaces to understand the origins of threshold voltage shifts in organic field-effect transistors - Mathijssen, Simon G. J.; Spijkman, Mark-Jan; Andringa, Anne-Marije; Hal, Paul A. van; McCulloch, Iain; Kemerink, Martijn; Janssen, René A. J.; Leeuw, Dago M. de (Advanced materials, 2010)
The semiconductor of an organic field-effect transistor is stripped with adhesive tape, yielding an exposed gate dielectric, accessible for various characterization techniques. By using scanning Kelvin probe microscopy we reveal that trapped charges after gate bias stress are located at the gate dielectric and not in the semiconductor. Charging of the gate dielectric is confirmed by the fact that the threshold voltage shift remains, when a pristine organic semiconductor is deposited on the exposed gate dielectric of a stressed and delaminated field-effect transistor.